Needs Analysis: Development of Songs Using Acoustic Music for Language Introduction for 5-6 Year Old Children in Kindergarten - Luthfi, Tasyfiah Aliya; Sumarni, Sri; Safitri , Erna Retna (FKIP - Universitas Riau, 2025)
This study aims to analyze the need for developing learning media in the form of acoustic music-based songs to support language acquisition in children aged 5–6 years in kindergarten. Language and music are essential components of early childhood development, as songs serve not only as entertainment but also as tools for stimulating cognitive, emotional, and linguistic growth. Using a qualitative descriptive approach through interviews and observations with teachers and students at Pembina 5 State Kindergarten in Palembang and several other kindergartens, the study found that songs are frequently used in learning activities and are considered effective in improving children’s language, cognitive, and motor skills. The children showed great enthusiasm for singing, particularly when accompanied by acoustic instruments such as guitars and ukuleles, which created a more interactive and enjoyable learning atmosphere. Teachers also highlighted the need for new acoustic songs designed to match the vocal characteristics and thematic learning needs of young children. These findings suggest that developing acoustic music-based songs is important as an innovative learning medium that can enhance children’s language literacy, foster creativity, and increase active participation in the classroom. Overall, acoustic music offers a more authentic and engaging approach to early language learning.